2016
DOI: 10.1111/mec.13670
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere length reveals cumulative individual and transgenerational inbreeding effects in a passerine bird

Abstract: Inbreeding results in more homozygous offspring that should suffer reduced fitness, but it can be difficult to quantify these costs for several reasons. First, inbreeding depression may vary with ecological or physiological stress and only be detectable over long time periods. Second, parental homozygosity may indirectly affect offspring fitness, thus confounding analyses that consider offspring homozygosity alone. Finally, measurement of inbreeding coefficients, survival and reproductive success may often be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 84 publications
(173 reference statements)
5
73
1
Order By: Relevance
“…Correlations between maternal heterozygosity and reproductive metrics may therefore be difficult to detect in marine turtles without controlling for variance in rates of capital accumulation (Broderick et al ., ). However, with sufficient long‐term data, it might be possible to test the hypothesis that heterozygosity affects efficiency at accumulating energy capital, and thereby remigration frequency and reproductive success, or to use biomarkers of stress such as telomeres (Plot et al ., ; Bebbington et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Correlations between maternal heterozygosity and reproductive metrics may therefore be difficult to detect in marine turtles without controlling for variance in rates of capital accumulation (Broderick et al ., ). However, with sufficient long‐term data, it might be possible to test the hypothesis that heterozygosity affects efficiency at accumulating energy capital, and thereby remigration frequency and reproductive success, or to use biomarkers of stress such as telomeres (Plot et al ., ; Bebbington et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Another genetic factor that has been suggested to affect telomere length is inbreeding depression (e.g., with long telomeres and high somatic telomerase levels throughout the body). For example, Bebbington et al . analyzed molecular inbreeding data on Seychelles warblers ( A. sechellensis ) and showed that inbreeding negatively affects telomere length (using qPCR).…”
Section: Telomere Regulation and Dynamics: Telomerase And Other Mechamentioning
confidence: 99%
“…Blackburn, Greider, and Szostak won the Nobel Prize for telomere and telomerase research, there has been a monumental increase in the research output on the associations between telomeres and a broad range of biomedical health‐related and other biological phenomena. These areas range from cancer and disease research, oxidative stress biochemistry, assisted reproductive technologies, developmental biology, epigenetic control of telomere length, and in‐ and outbreeding genetics to life history evolution . In many cases, these phenomena are interpreted to be causally linked to telomere dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, studies of wild populations have informed understanding of how early‐life environments shape individual senescence patterns (Cooper & Kruuk, ; Lemaitre et al, ; Nussey, Froy, Lemaitre, Gaillard, & Austad, ). This understanding has been further improved by quantification of extrinsic effects through biomarkers that reflect ecological effects that are otherwise difficult to measure (Bebbington et al, ; Spurgin et al, ).…”
Section: Introductionmentioning
confidence: 99%